A new species, four new combinations, a lectotypification, phylogenetic analysis, and a key to the species in Funkiella (Orchidaceae, Cranichideae, Spiranthinae) - Salazar, Gerardo A.; Fortanelli-Martínez, Javier; Castillo-Lara, Pedro; Cabrera, Lidia I. (Phytotaxa, 2025)
A new species of the genus Funkiella from the region of the Área de Protección de Flora y Fauna Sierra de Álvarez, San Luis Potosí, Mexico, is described and illustrated as F. garciaperezii Salazar, Fortanelli & Cast.-Lara. Our phylogenetic analysis of nuclear (nrITS) and plastid DNA sequences (matK-trnK, trnL-trnF) recovered it as the sister of a clade consisting of all the species of Funkiella analyzed excepting F. rubrocalosa, which occupies the earliest-diverging position of the genus. Morphologically, F. garciaperezii is similar to F. faucisanguinea (Dod) Salazar (comb. nov.), but differs from the latter in the glabrous peduncle, rachis, ovary, and outer surface of the sepals (vs. sparsely glandular-pubescent); the dull brownish thickened area on the labellum hypochile (vs. bright red thickened area); the prominent digitiform papillae on the ventral surface of the column (vs. short digitiform papillae); and the proportionately shorter, parallel pollinia (vs. long linear, divergent pollinia). New combinations in Funkiella are provided for Ecuadoria intagana, Galeottiella constricta, Spiranthes faucisanguinea, and Spiranthes muscicola, and Spiranthes porphyricola is lectotypified. An identification key to the 14 accepted species of Funkiella is provided.